2020
DOI: 10.5334/bc.37
|View full text |Cite
|
Sign up to set email alerts
|

Residential retrofit in the climate emergency: the role of metrics

Abstract: This paper examines whether current residential retrofit metrics are fit for purpose and if they can help deliver swift and significant cuts in carbon emissions. Information is presented on metrics used for a variety of UK and European Union building and building retrofit standards and evaluation and assessment tools. An analytical approach is developed that offers a simplified set of four key aspects of metrics: scope, headline measurement, normalisation factor and timescale. This helps to unpack the complexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…For example, training to meet minimum standards, plus training to exceed these to meet likely future standards, in addition to highly stringent energy efficiency standards to achieve net zero, over three or more tiers, could better prepare the workforce than only training to meet current building regulation standards as a target. It is ineffective if the standards required to meet zero-carbon targets are only understood by specialists (Fawcett & Topouzi 2020). Simpson et al Buildings and Cities DOI: 10.5334/bc.106 Beyond technical capabilities, the capabilities required to manage resources and people effectively were salient in the data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, training to meet minimum standards, plus training to exceed these to meet likely future standards, in addition to highly stringent energy efficiency standards to achieve net zero, over three or more tiers, could better prepare the workforce than only training to meet current building regulation standards as a target. It is ineffective if the standards required to meet zero-carbon targets are only understood by specialists (Fawcett & Topouzi 2020). Simpson et al Buildings and Cities DOI: 10.5334/bc.106 Beyond technical capabilities, the capabilities required to manage resources and people effectively were salient in the data.…”
Section: Discussionmentioning
confidence: 99%
“…To be effective, Clarke et al (2020) suggest capability development for low-energy construction needs to move away from narrow capabilities and specific tasks and to take more standardsfocused approaches with broad occupational profiles. In the UK, the measures intended to drive change in retrofit, stemming from the Clean Growth Strategy and Energy Performance Certificates, need to be more widely understood, not remaining the preserve of specialists alone (Fawcett & Topouzi 2020). As technical building standards progress, they can drive innovation, potentially as part of a group of policies aiming to improve building performance (Gann et al 1998).…”
Section: Rmi Retrofit Practitioners and Capabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Estrella Guillén et al [20] compared different metrics for benchmarking energy and comfort and showed that they are not interchangeable, suggesting that different metrics can drastically affect the perception of a building's performance. Likewise, Fawcett and Topouzi [21] investigated the role of metrics used in domestic retrofit and whether they are fit-for-purpose, finding that there is a particular importance in the choice between measurements of carbon and of energy, which is corroborated by [22]. Simpson et al (2020) performed a bibliometric analysis of data-centric research in retrofit across Northwestern Europe, looking at computational models, monitoring frameworks, and statistical analyses [23].…”
Section: Data and Modellingmentioning
confidence: 99%
“…Rebates and information are seemingly insufficient to overcome the barriers to major investments in home energy efficiency for most homeowners. Indeed, despite the rollout of retrofit programs in most advanced economies in recent decades, few countries have seen large‐scale residential retrofit adoption with significant energy efficiency gains (Fawcett and Topouzi 2020). This is not surprising when considering the many barriers to performing retrofits: high upfront costs, long payback times, low energy literacy, imperfect information, low awareness of the multi‐dimensional benefits of energy efficiency retrofits, competing priorities for home renovation investments (e.g., cosmetic upgrades), the availability of trusted contractors, the hassles and disruptions associated with major retrofits, and more (IPCC 2014; Regnier et al 2018).…”
Section: Introductionmentioning
confidence: 99%